2021
DOI: 10.1002/cncr.33548
|View full text |Cite
|
Sign up to set email alerts
|

Adults are just big children: What we can learn about quality end‐of‐life care from pediatrics

Abstract: Because caring for children involves caring for families, pediatricians necessarily integrate individual patient, family, and community perspectives into medical care. This editorial considers how that pediatric family‐centered practice underscores emerging definitions of “quality” end‐of‐life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…What is feasible and pragmatic to measure does not necessarily equate with what is most important to key stakeholders. [37][38][39] Indeed, many highly prioritized quality measures for children with advanced cancer fall within the auspices of what is currently aspirational and not yet feasible in practice (Figure 1). An added wrench in quality measurement is that, depending on key stakeholder interests, what is viewed as a priority for achieving value-based care may greatly differ.…”
Section: Quality Measure Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…What is feasible and pragmatic to measure does not necessarily equate with what is most important to key stakeholders. [37][38][39] Indeed, many highly prioritized quality measures for children with advanced cancer fall within the auspices of what is currently aspirational and not yet feasible in practice (Figure 1). An added wrench in quality measurement is that, depending on key stakeholder interests, what is viewed as a priority for achieving value-based care may greatly differ.…”
Section: Quality Measure Developmentmentioning
confidence: 99%
“…The divergence between our two sets of measures illustrates a tension in quality measurement between the pragmatic and the aspirational. What is feasible and pragmatic to measure does not necessarily equate with what is most important to key stakeholders 37–39 . Indeed, many highly prioritized quality measures for children with advanced cancer fall within the auspices of what is currently aspirational and not yet feasible in practice (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Although a set of quality measures exists for adults with advanced cancer, we previously found that quality measures for adults did not directly translate to the pediatric context owing to developmental considerations in children, the delicate balance of parent and child dyadic decision-making, and what families fundamentally value about advanced childhood cancer care . Hence, to optimize care value, there is an imminent need to establish end-of-life care quality measures that attend to the preferences and priorities of children with cancer and their families …”
Section: Introductionmentioning
confidence: 99%
“…4 Hence, to optimize care value, there is an imminent need to establish end-of-life care quality measures that attend to the preferences and priorities of children with cancer and their families. 13 In 2 previous studies, 4,6 we engaged stakeholders in defining and refining what constitutes high-quality end-of-life care for children with cancer. We thereby derived 28 candidate quality measures and narrowed these subsequently to a set of very important measures.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in communication and decision making between adults and children at various developmental stages, distinct health insurance and reimbursement policies, and differential access to palliative and hospice services may render QMs for adults of limited applicability to children. 10 To address this knowledge gap, we previously engaged key stakeholders, including patients, parents, and health care professionals, to identify attributes of high-quality end-of-life care for children with cancer. 11 This study yielded 26 candidate patient-centered measures of high-quality care.…”
Section: Introductionmentioning
confidence: 99%